Tibetan herbal medicine Oxytropis falcata Bunge ameliorates hypoxic pulmonary hypertension in rats via regulation of intestinal microbiota and metabolites - He, Yuxin; Guo, Zixu; Xue, Hua; Zhu, Xia; Luo, Tian; Bai, Zhenzhong; Ma, Lan; Cao, Xuefeng (Frontiers in Microbiology, 2025)
BackgroundHypoxic pulmonary hypertension (HPH) is a severe high-altitude disorder with limited therapeutic options. This study investigated the therapeutic mechanisms of Oxytropis falcata Bunge (OFB), a traditional Tibetan herbal medicine, in a rat model of HPH, focusing on its effects on endogenous metabolites and gut microbiota.MethodsHPH was induced in male Sprague–Dawley rats exposed to chronic hypoxia. Animals were randomly assigned to normoxic control, hypoxic model, OFB-treated, or Rhodiola-treated groups. Serum metabolomics (LC-MS) and 16S rRNA sequencing of fecal microbiota were performed. Cardiopulmonary parameters including RVSP and RVHI were assessed, and pulmonary arterial ultrastructure was examined.ResultsOFB significantly attenuated HPH-induced elevations in RVSP and RVHI and mitigated pulmonary arterial remodeling. Metabolomic analysis identified 25 differentially regulated metabolites in HPH, primarily involved in pyrimidine metabolism, which were largely restored by OFB. OFB also reversed HPH-induced gut microbiota dysbiosis, restoring microbial diversity and composition toward normoxic levels. Correlation analysis revealed significant associations between specific bacterial taxa and altered metabolites.ConclusionsThese findings suggest that OFB exerts therapeutic effects against HPH by modulating gut microbiota dysbiosis and restoring metabolic homeostasis, particularly within pyrimidine metabolism. The observed gut–lung axis interactions may underlie these effects, offering novel mechanistic insights and supporting the potential clinical development of OFB as a microbiota-targeted therapy for HPH.